Smoking status and anti-inflammatory macrophages in bronchoalveolar lavage and induced sputum in COPD - Kunz, Lisette IZ (BioMed Central, 2011)
BACKGROUND: Macrophages have been implicated in the pathogenesis of COPD. M1 and M2 macrophages constitute subpopulations displaying pro- and anti-inflammatory properties. We hypothesized that smoking cessation affects macrophage heterogeneity in the lung of patients with COPD. Our aim was to study macrophage heterogeneity using the M2-marker CD163 and selected pro- and anti-inflammatory mediators in bronchoalveolar lavage (BAL) fluid and induced sputum from current smokers and ex-smokers with COPD. METHODS: 114 COPD patients (72 current smokers; 42 ex-smokers, median smoking cessation 3.5 years) were studied cross-sectionally and underwent sputum induction (M/F 99/15, age 62 ± 8 [mean ± SD] years, 42 (31-55) [median (range)] packyears, post-bronchodilator FEV(1 )63 ± 9% predicted, no steroids past 6 months). BAL was collected from 71 patients. CD163(+ )macrophages were quantified in BAL and sputum cytospins. Pro- and anti-inflammatory mediators were measured in BAL and sputum supernatants. RESULTS: Ex-smokers with COPD had a higher percentage, but lower number of CD163(+ )macrophages in BAL than current smokers (83.5% and 68.0%, p = 0.04; 5.6 and 20.1 ×10(4)/ml, p = 0.001 respectively). The percentage CD163(+ )M2 macrophages was higher in BAL compared to sputum (74.0% and 30.3%, p < 0.001). BAL M-CSF levels were higher in smokers than ex-smokers (571 pg/ml and 150 pg/ml, p = 0.001) and correlated with the number of CD163(+ )BAL macrophages (Rs = 0.38, p = 0.003). No significant differences were found between smokers and ex-smokers in the levels of pro-inflammatory (IL-6 and IL-8), and anti-inflammatory (elafin, and Secretory Leukocyte Protease Inhibitor [SLPI]) mediators in BAL and sputum. CONCLUSIONS: Our data suggest that smoking cessation partially changes the macrophage polarization in vivo in the periphery of the lung towards an anti-inflammatory phenotype, which is not accompanied by a decrease in inflammatory parameters.